Alcoholic preparation for hand hygiene in ophthalmic day hospitals: an applied research - Souza Santos, Thalita; Costa, Roberta (International Journal of Infection Control, 2026)
Objective: To define and validate the optimal consumption of alcoholic preparation for ophthalmic day hospitals based on the minimum opportunities for hand hygiene (HH) required during the care provided in the Diagnostic Imaging Center and the Surgical Center of an ophthalmic day hospital. Method: An applied research was developed between May and July 2021. To conduct the research, six phases were defined: 1) Establishment of the conceptual structure; 2) Mapping the minimum opportunities for HH; 3). Validation of the mapping of minimum opportunities; 4). Calculation of the ideal minimum consumption of alcoholic preparation for HH; 5) Comparison of results with the institution’s data. 6). Development of the guide. Nineteen health professionals participated in this study between the validation stages in the institution and validation with specialists. Results: We identified that the minimum consumption of alcoholic preparation is: 63 mL/surgical patient undergoing local anesthesia, 126 mL/surgical patient submitted to local anesthesia with sedation, 123 mL/surgical patient submitted to general anesthesia, 15 mL/patient submitted to unprepared examination, 21 mL/patient submitted to prepared examination, and 57 mL/patient submitted to examination with contrast. Discussion: The profile of the patient, the institution, and the care provided may directly influence the number of opportunities for HH, which, in turn, directly impacts the reference of alcohol preparation consumption. Therefore, a single goal cannot translate the need for all of them. This condition refers to the need to determine specific consumption goals by patient profile and procedure so that the alcohol preparation consumption indicator effectively reflects the quality of care achieved in HH.